Indefiniteness Constraints of (Monotransitive) Ov-Agents in Balinese - Udayana, I Nyoman (Jurnal Kajian Bali (Journal of Bali Studies), 2012)
Abstract The study focuses on monotransitive objective-focus(OV) agents in Balinese. The evidence shown in thisstudy supports the claim that monotransitive OV agentsare subject to indefiniteness conditions. These conditionsare motivated by the fact that monotransitive OV agentsappear with verbs which are zero-marked. AV agents, onthe other hand, appear with verbs which are inherentlymarked. They are not sensitive to the condition. Nor areditransitive OV agents whose verbs get marked either viaapplicativization or causativization process. Looked at inthis way, ditransitive OV agents behave like AV agents ingeneral. OV agents contains syntactically independent NPswhich may be reduced to a bare N or expanded into a morecomplex NP, confirming that they are not analyzable as anincorporated or cliticized material.
Keywords: (in)definiteness condition, OV /AVagent, monotransitive/ditransitive, applicativization/ cusativization process